Plautus alle (Alcidae) - Verhalten am Ruheplatz - Georg Rüppell (IWF (Göttingen), 1969)
(en)Here we see the auk Plautus alle in its resting-place in front of the nesting-holes. The auklets demonstrate several ways of behaviour; chorus singing, impressive walking, billing, grooming, and resting. The mandible pouches of auks returning from the sea are filled with food. The cliff landings of the birds were shot at a speed of 60 p/s.